Nutrition and HIV/AIDS Implication for Treatment, Prevention and Cure - Dumais, Nancy (IntechOpen, 2020)
This edited volume, "Nutrition and HIV/AIDS - Implication for Treatment, Prevention and Cure", is a collection of reviewed and relevant research chapters, offering a comprehensive overview of recent developments in the field. The book comprises single chapters authored by various researchers and edited by an expert active in the research area. All chapters are complete in themselves but united under a common research study topic. This publication aims at providing a thorough overview of the latest research efforts by international authors and opening new possible research paths for further novel developments.